FIRST RECORD OF MINUCA BREVIFRONS (STIMPSON, 1860) (DECAPODA: OCYPODIDAE) IN ECUADOR - Ramos-Veliz, John (2022)
The occurrence of the fiddler crab Minuca brevifrons Stimpson, 1860 in Ecuador (Eloy Alfaro, province of Manabi) is reported for the first time. The organisms had a small patchy distribution sharing habitat in a mangrove area destined for the harvesting of the blue crab Cardisoma crassum Smith, 1870, where they established an inquilinism relationship since it lives in burrows built by the blue crab. The identification of specimens was based on taxonomic characters and bibliographic review, where the distinctive morphological feature is the width of its forehead and the oblique crest on the palm of the greater chela. This record extends its distribution on the Pacific side to Ecuador, contributing to the knowledge of biodiversity at the regional level. It is recommended to increase the studies aimed at the diversity of crustaceans at the local level to understand their biology, dynamics, and ecological interactions.